Making Community-Based Research Work: Lessons Learned from a Liberal Arts College - Carol L. Clark (The University of Alabama, 2022)
Trinity College launched the Community Learning Research Fellows Program in 2011 to support undergraduate community-based research (CBR). Our goal was to create an environment that supports high-quality undergraduate research consistent with the principles of community learning. Our strategy focused on building the right type of collaborative relationships among the different actors involved in CBR. We learned three important lessons in our efforts to support these relationships: (1) The community perspective must be integrated into the structure of the program to lend it authority; (2) Peer learning should be used to better prepare students to meet the challenges of CBR; and (3) Expanding the collaborative learning model to include a diverse group of participants empowers students to construct knowledge with and for their community partners. The broader implications of these lessons are discussed in the conclusion.